Planeación Financiera a la Cooperativa de Ahorro y Crédito Bansur de la Parroquia San Lucas, Cantón Loja periodo 2014-2015 - QUIZHPE ORDOÑEZ, JHULIANA MICHELLE (2016)
The present thesis work named financial planning is same to that held it to the cooperative savings and credit "Bansur" of the parish San Lucas of the Loja Canton for the purpose of applying a "financial analysis, as well as the planning of the financial statements, through the application of technical and financial tools, with the aim that the directors and management have a useful tool for decision-making appropriate to future." To comply with this thesis work was necessary to develop the following specific objectives such as:Apply horizontal and vertical analysis to the financial statements periods 2012-2013 of the cooperative BANSUR credit, through the application of indicators financial periods 2012-2013. As a second objective is: develop operating and financial leverage to the cooperative. And as third and final goal is to make balance sheets proformas for cooperativa de ahorro y crédito, in such a way that allows to visualize future financial results. But for the realization of this objective was necessary develop a forecast of revenue and expenses to establish program input and output currency and thereby develop the cash budget, using the percentage method, which was based on the monthly historical data collection of revenues and expenses of the economic activity of the cooperative and were used to predict the inputs and outputs of the cash being which underpin the Projected cash budget. 5 The States Pro form, it developed them taking into account the percentage method of forecasted data from the years 2014-2015, in showing the results State revenues and expected expenses; While the State's financial situation shows the projected financial position at the end of an economic period. Likewise for the development of this thesis work used methods such as: the scientist who allowed to strengthen the knowledge and skills; deductive which helped to determine the General aspects of the financial planning; inductive served to know the characteristics of the institution; analytical and synthetic helped to sort the information by the entity and to draw up conclusions and recommendations; mathematician and statistician allowing to perform the respective calculations, in addition to representing the data obtained from the analysis. At the end of the thesis work are presented the conclusions and recommendations that will be taken into account by the directors of the cooperative to establish a financial planning that will help to improve the financial position and financial cooperative entity